Effectiveness of Sludge Microbial Consortia in the Bioremediation of Detergent-Containing Launderette Wastes - Yan Ramona; Esti Arisetya Dewi; Yenni Ciawi; I Wayan Budiarsa Suyasa (Cassowary, 2022)
This project investigated the potential of microbial consortia obtained from several sources to reduce or eliminate detergent concentration in the wastes of launderette businesses found in the capital city of Bali. Before being used as active starters, the consortium of microbiota contained in the 3 waste sources was enriched in a medium containing (g/l); 1 glucose, 0.05 K2HPO4, 0.05 KH2PO4, 0.05 (NH4)2[Fe(SO4)2].6H2O, 0.01 MgSO4, 0.01 yeast extract, 1800 mL distilled water, and 200 mL of wastewater of launderette industries. An important parameter used to indicate microbial growth was the level of the volatile solid substrate (VSS) in the enrichment medium. The microbial culture that showed the highest VSS only was further investigated in the main experiments by observing its effectiveness in reducing detergent linear alkyl-benzenesulfonates (LAS) and the chemical oxygen demand (COD) of launderette wastes. In this project, microbial consortia developed from detergent-containing launderette wastes were the most active starter to decrease the COD and LAS detergent content following 7 days of exposure. This starter (microbial consortia developed from this launderette waste) showed the highest value of VSS when compared to those collected from other sources, and this was reached on day 4. In the main experiment, 85.5% and 91.9% reduction of LAS and the COD of the wastes, respectively, were observed following exposure of the launderette waste with this culture starter. This indicated that these microbial consortia have the possibility to be developed as a potential starter in larger scales of detergent bioremediation.